Empowerment of PKK in Keliling Benteng Ulu Village, West Martapura District by Utilizing TOGA into an Instant Drink with Commercial Value - Isnaini; Asnawati; Azma Rosida; Emmi Erliyanti; Nabilla Azzahra Ariady; Dinda Rohama; Jeniar Atmadela; Zahra Aprillita (Jurnal Pengabdian Masyarakat Formosa, 2023)
Keliling Benteng Ulu Village (KBU) in West Martapura Subdistrict, Banjar Regency, South Kalimantan, is an adopted village under the supervision of the Undergraduate Medical Study Program, Faculty of Medicine, Lambung Mangkurat University. Previously, they distributed TOGA plant seeds and conducted educational sessions on their benefits. In the current phase, five residents are selected for training in creating instant herbal drinks from TOGA plants, supported with necessary tools. The resulting herbal drink, named "Jamu WIRAS," is linked with the "KBU Sehat" SME group. After initial training on creating and packaging, participants will autonomously produce the drink, providing photo and video documentation. A WhatsApp group facilitates communication between the service team and SME group. The marketing involves the district-level Women's Welfare Organization's assistance and integration into various events.